Risk factors for recurrent primary biliary cirrhosis after liver transplantation: A systematic review and meta-analysis. Issue 3 (March 2021) - Li, Xiaocheng; Peng, Jing; Ouyang, Renbin; Yang, Yaowei; Yu, Chengdong; Lin, Huapeng
Abstract: Background: Recurrent primary biliary cirrhosis (PBC) is frequently observed in patients with PBC after liver transplantation (LT). We performed a meta-analysis to evaluate the risk factors for PBC recurrence. Methods: We searched the EMBASE, PubMed and the Cochrane Library databases for studies published before August 2020. Studies that identified the risk factors of PBC recurrence were eligible for inclusion. We extracted the hazard ratio (HR) data with 95% confidence intervals (CI) for the risk factors. Results: Our meta-analysis included 6 studies, which comprised 3184 patients (88.5% females) who underwent liver transplantation from 1982 to 2017, and of these patients, 935 (29.4%) developed PBC recurrence. The use of tacrolimus (HR = 2.62, 95% CI = 1.35, 5.09) and preventive ursodeoxycholic acid (UDCA) (HR = 0.40, 95% CI = 0.28, 0.57) were significantly associated with the risk of PBC recurrence based on the pooled analysis of the results obtained from the multivariate analysis. Conclusions: The use of tacrolimus is associated with an increased risk of PBC recurrence. Preventive UDCA after LT for PBC can help to prevent disease recurrence.